FINLANDIA VS KOREA SELATAN : DUA KUTUB BERBEDA DALAM DUNIA PENDIDIKAN - Laela; Nazla; Sholeh Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the fundamental differences between the Finnish and South Korean education systems, often viewed as polar opposites in modern education. The aim of this study is to analyze the key characteristics of both systems through a qualitative approach based on literature review. Data were collected from relevant scientific journals, books, and official reports and then analyzed using content analysis techniques to uncover the educational philosophy, study load, teacher role, and evaluation mechanisms implemented in each country. The results show that Finland implements an education system that emphasizes student well-being, teacher autonomy, short study hours, and formative evaluation without a focus on national exams. In contrast, South Korea adopts a competition-oriented system, long study hours, reliance on tutoring, and rigorous evaluations such as Suneung, which significantly determine students' futures. Both models produce high academic achievement, but through different approaches. This study concludes that no single system can be used as an absolute benchmark; integrating Finnish well-being values with South Korea's hard work ethic can be an important consideration in designing more balanced education policies in other countries, including Indonesia.